The Impact of Teacher Competency Management Development on Educational Effectiveness in Elementary Schools - Ratnawati Susanto (MIMBAR PGSD Undiksha, 2025)
The low effectiveness of educational management negatively affects learning quality in elementary schools, creating an urgent need to evaluate the impact of teacher competency development programs on school performance. This study aims to analyze the effect of teacher competency development on the effectiveness of educational management. This research employs a quantitative survey design. The sample consisted of 250 elementary school teachers. Data were collected using closed-ended questionnaires based on teacher competency indicators (pedagogical, professional, social, and personal) and educational management effectiveness indicators (planning, organizing, implementing, and evaluating). Data analysis was conducted using descriptive statistics with SPSS version 29.0, multiple linear regression, and Structural Equation Modeling Partial Least Square (SEM-PLS). The results indicate that teacher competency significantly influences educational management effectiveness, contributing 56–64%. Professional competency was the most dominant in the organizing aspect (β = 0.32; p = 0.000), followed by personal, pedagogical, and social competencies. Implementation had the highest R² value (0.64), while evaluation had the lowest R² (0.56), yet remained significant. In conclusion, sustainable and practice-oriented teacher competency development plays a crucial role in enhancing learning quality and educational management effectiveness. The study implies that teacher development programs based on mentoring, collaboration, and school leadership support strengthen overall education quality.